DESKRIPSI PEDAGOGIC CONTENT KNOWLEDGE MAHASISWA PENDIDIKAN MATEMATIKA MELALUI MICROTEACHING - Alfonsa Maria Abi (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
Pedagogical content knowledge (PCK) is one of the important elements in improving students' understanding because teachers are required to master teaching materials or subject matter (content) and master teaching science (pedagogy). As a mathematics education, students are also required to have PCK skills. This type of research is qualitative descriptive with the aim of analyzing the PCK ability of mathematics education students in microteaching courses as a prerequisite for carrying out PPL activities in schools. The subjects of this study were 34 mathematics education students taking microteaching courses for the 2015/2016 academic year. The results showed that mathematics education students were able to coordinate and compile all parts of the lesson plan well, especially in terms of systematics. This means that they have knowledge of the curriculum well, understand students according to the level of knowledge in secondary schools and know how to conduct evaluations. The results of the description of the implementation of the learning process, it was found that students were still lacking in teaching knowledge and about content, the implementation of learning was not in accordance with the draft that had been compiled and were unable to understand well how to present material according to the learning strategy in the lesson plan. Student PCK in the learning process still has many deficiencies, especially in the content, teaching and student sections.